Granulocyte Colony-Stimulating Factor (G-CSF) Protects Oligpdendrocyte and Promotes Hindlimb Functional Recovery after Spinal Cord Injury in Rats - Kadota, Ryo; Koda, Masao; Kawabe, Junko; Hashimoto, Masayuki; Nishio, Yutaka; Mannoji, Chikato; Miyashita, Tomohiro; Furuya, Takeo; Okawa, Akihiko; Takahashi, Kazuhisa; Yamazaki, Masashi (PLOS ONE, 2012)
Background Granulocyte colony-stimulating factor (G-CSF) is a protein that stimulates differentiation, proliferation, and survival of cells in the granulocytic lineage. Recently, a neuroprotective effect of G-CSF was reported in a model of cerebral infarction and we previously reported the same effect in studies of murine spinal cord injury (SCI). The aim of the present study was to elucidate the potential therapeutic effect of G-CSF for SCI in rats. Methods Adult female Sprague-Dawley rats were used in the present study. Contusive SCI was introduced using the Infinite Horizon Impactor (magnitude: 200 kilodyne). Recombinant human G-CSF (15.0 µg/kg) was administered by tail vein injection at 1 h after surgery and daily the next four days. The vehicle control rats received equal volumes of normal saline at the same time points. Results Using a contusive SCI model to examine the neuroprotective potential of G-CSF, we found that G-CSF suppressed the expression of pro-inflammatory cytokine (IL-1 beta and TNF- alpha) in mRNA and protein levels. Histological assessment with luxol fast blue staining revealed that the area of white matter spared in the injured spinal cord was significantly larger in G-CSF-treated rats. Immunohistochemical analysis showed that G-CSF promoted up-regulation of anti-apoptotic protein Bcl-Xl on oligpodendrocytes and suppressed apoptosis of oligodendrocytes after SCI. Moreover, administration of G-CSF promoted better functional recovery of hind limbs. Conclusions G-CSF protects oligodendrocyte from SCI-induced cell death via the suppression of inflammatory cytokines and up-regulation of anti-apoptotic protein. As a result, G-CSF attenuates white matter loss and promotes hindlimb functional recovery.